SOCIAL ENTERPRISE FOR EMPOWERMENT OF WOMEN FROM ETHNIC MINORITY: CHALLENGES AND POSSIBILITIES - Christauskas, Česlovas; Žilionė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The empowerment of women and the improvement of their political, social, economic and health status is a highly important and is one of the Global Sustainable Goals. Gender Equality index 2020 of EU-28 is 67.9, slowly increasing (European Institute for Gender Equality, 2021). Although there are some researches related to women empowerment and economic development (Siba, 2019, Hemalatha, 2020, Doss, Malapit, & Comstock, 2020, etc.) or social entrepreneurship (Biggeri, Testi, Bellucci, During, & Persson, 2018; Briar-Lawson, Miesing, & Ram, 2020, etc.), combining these two fields and especially adding women from ethnic minority is very rare in scientific researches.The aim of the paper is to highlight challenges and possibilities of social entrepreneurship for empowerment of women from ethnic minority.This paper is based on Erasmus+ project “Empowering Women from Ethnic Minorities Through Social Enterprises” (abbrev. EMwoSE) analysis of both quantitative and qualitative data retrieved in Ireland, United Kingdom, Germany, Greece, Italy, Lithuania and Turkey. International data gives to the paper additional value in picturing the bigger picture of the situation in European countries.However, women starting a social enterprise is itself contributing to women’s empowerment, assuming that social enterprise can be culturally more acceptable for women from ethnic minorities.